The Role of Al Hikmah Mosque Youth in Overcoming the Spread of Covid 19 in Learning the Qura’n - Maulydia Briegga Taniatara; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
Until now, it has not been found where the location of Muhammadiyah in Sidoarjo was founded, because the process of tracking the history of Muhammadiyah in Sidoarjo Regency has not yet been completed, because it faces a conflict of operational funds. Meanwhile, the branches of Candi and Rantung sub-districts of Buduran are under the guidance of the Sidoarjo sub-district branch.In the late 1970s, the term Muhammadiyah Regional Leadership emerged.And also in breaking the chain of spreading COVID-19, the youth of the Al-Hikmah Mosque, Sidoarjo Temple, carried out strict health protocols for the congregation of the Al-Hikmah Mosque.By providing a body temperature measuring device, washing hands before entering the mosque and also a hand senitaizer for the congregation.In addition, mosque youth always spray the rooms inside and outside the mosque using disinfectants to sterilize the environment.This study uses descriptive qualitative research methods.A qualitative approach is a research process to understand social or human problems by analyzing words to create a complex and comprehensive picture, and reporting detailed views of information obtained from sources of information in a natural environment.The Central Leadership of Muhammadiyah conveyed the guidance for Ramadan 1442 H/2021 AD in the COVID-19 emergency condition according to the Fatwa of the Tarjih Council and Tajdid of the Muhammadiyah Central Executive as attached and is an inseparable part of this Circular.